Self-care and perception of the diabetes treatment by people using insulin - Pamela dos Reis; Guilherme Oliveira de Arruda; Evelin Matilde Arcain Nass; Erika Santos Ratuchnei; Maria do Carmo Fernandez Lourenço Haddad; Sonia Silva Marcon (Universidade Federal de Santa Maria, 2020)
Objective: to understand the perception of people with Diabetes Mellitus using insulin about their self-care and the repercussion of treatment in their daily lives. Method: exploratory and descriptive research, with a qualitative nature, performed in a medium-sized municipality in the Southern Region of Brazil, with 16 people using insulin who were being monitored in Primary Care. Data were collected from May to July 2017, through semi-structured interviews and submitted to thematic analysis. Results: it gave rise to three categories that address the difficulties in changing life habits, the repercussions of insulin use in daily life and the obstacles experienced in the purchase of pharmaceutical inputs for treatment. Conclusion: the practice of self-care by people with Diabetes Mellitus using insulin is permeated by several difficulties, where the main one is the need for changes in lifestyle.